An Analysis of Politeness Strategies Used in Yes Day (2021) Movie - Selina Putri; Fitrawati Fitrawati (Universitas Negeri Padang, 2022)
This research aimed to find out the politeness strategies used in Yes Day (2021) movie. The research used descriptive qualitative method. The source of data was the Yes Day movie that focused on the script of movie. The data were all of the requesting utterances that uttered by all of the characters of Yes Day movie. The data were analysed using Brown and Levinson (1987) politeness theory. The researcher found four types of politeness strategies; they are bald on-record, positive politeness, negative politeness, off record strategy, and no don’t do the FTA. The result of the research showed that bald on-record was the most appeared strategy in Yes Day movie. Meanwhile, off record strategy was the least used strategy in Yes Day movie.